The Schooling and Labor Market Effects of Eliminating University Tuition in Ecuador - Teresa Molina; Ivan Rivadeneyra (Institute of Labor Economics (IZA), 2020)
This paper estimates the effects of a 2008 policy that eliminated tuition fees at public universities in Ecuador. We use a difference-in-differences strategy that exploits variation across cohorts differentially exposed to the policy, as well as geographic variation in access to public universities. We find that the tuition fee elimination significantly increased college participation and affected occupation choice, shifting people into higher-skilled jobs. We detect no statistically significant effects on income. Overall, the bulk of the benefits of this fee elimination were enjoyed by individuals of higher socioeconomic status.
Keywords: I23; I24; I28; O15; 330; higher education; tuition reduction; Ecuador